2023
DOI: 10.1101/2023.11.29.569223
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fecal transplant allows transmission of the gut microbiota in honey bees

Amélie Cabirol,
Audam Chhun,
Joanito Liberti
et al.

Abstract: The gut of honey bees is colonized by symbiotic bacteria during the first days of adult life, once bees have emerged from their wax cells. Within five days, the gut microbiota becomes remarkably stable and consistent across individual bees. Yet, the modes of acquisition and transmission of the gut microbiota are to be confirmed. Few studies suggested bees could be colonized via contact with fecal matter in the hive and via social interactions. However, the composition of the fecal microbiota is still unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…Here, we showed that live S. alvi could be consistently isolated in large concentrations in the feces of honey bees over time (Fig 4), which suggests that bacteria typically settling in the proximal gut also accumulate in the rectum, probably due to shedding of gut tissues [51]. This has since been confirmed by another study carried out by our group that characterized the fecal microbiota of honey bees and showed that all major genera of the gut microbiota are also found in the feces [52]. Considering that caged honey bees do not defecate, it is likely that bacterial accumulation was exacerbated in the rectum of individuals reared in the laboratory.…”
Section: Plos Biologysupporting
confidence: 56%
“…Here, we showed that live S. alvi could be consistently isolated in large concentrations in the feces of honey bees over time (Fig 4), which suggests that bacteria typically settling in the proximal gut also accumulate in the rectum, probably due to shedding of gut tissues [51]. This has since been confirmed by another study carried out by our group that characterized the fecal microbiota of honey bees and showed that all major genera of the gut microbiota are also found in the feces [52]. Considering that caged honey bees do not defecate, it is likely that bacterial accumulation was exacerbated in the rectum of individuals reared in the laboratory.…”
Section: Plos Biologysupporting
confidence: 56%